1991
DOI: 10.3109/01485019108987625
|View full text |Cite
|
Sign up to set email alerts
|

Histochemistry of Human Urethral Glands

Abstract: Human urethral glands were reacted histochemically and immunohistochemically to identify glycoproteins, some androgen metabolic enzymes, and VIP-like immunoreactivity. Neutral/acid mucosubstances were detected mainly in the apical cytoplasm of the principal cells. 3 beta-, 17 beta-, and 3 alpha-hydroxysteroid dehydrogenase, G6PD, and 6PGD reactivity were intense in all the glandular epithelium. Small amounts of VIP-positive fibers were noted around the secretory elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Although the functional importance of seminal MG1 in reproductive physiology is completely unknown, it could be hypothesized that, like other mucins (Lagow et al 1999), it influences the sperm transport in the male and female genital tracts. The secretions of bulbourethral glands, although never analysed separately, are believed to consist of a mixture of acidic mucins, as deduced by studies with conventional histochemistry (Riva et al 1981;Sirigu et al 1991). Previous immunohistochemical studies (Cossu et al 1994) demonstrated the blood group reactive substances ABH, Le-a, and Le-b in the mucous granules of both urethral and bulbourethral glands in conformity with the blood group type and secretor status, and hypothesized that such saccharide groups were associated with mucins.…”
Section: Discussionmentioning
confidence: 99%
“…Although the functional importance of seminal MG1 in reproductive physiology is completely unknown, it could be hypothesized that, like other mucins (Lagow et al 1999), it influences the sperm transport in the male and female genital tracts. The secretions of bulbourethral glands, although never analysed separately, are believed to consist of a mixture of acidic mucins, as deduced by studies with conventional histochemistry (Riva et al 1981;Sirigu et al 1991). Previous immunohistochemical studies (Cossu et al 1994) demonstrated the blood group reactive substances ABH, Le-a, and Le-b in the mucous granules of both urethral and bulbourethral glands in conformity with the blood group type and secretor status, and hypothesized that such saccharide groups were associated with mucins.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the prostate and the urethral (Littre's) glands, Cowper's glands originate from the endoderm of the urogenital sinus (Spring-Mills & Hafez, 1980). The prostate and the urethral glands are androgen dependent organs (Sirigu et al, , 1991. Coffey (1988) asserts that the bulbourethral glands, too, are androgen dependent organs, even if no data showed that these glands behave as typical androgen target structures.…”
Section: Discussionmentioning
confidence: 99%
“…The histological demonstration of 3P-HSD and 17fi-HSD activities does not denote the occurrence of androgen activation, for the reason that these enzymes are involved not only in the reductive, but also in the oxidative process, which leads to the formation of inactive steroids. They have been in fact detected in both androgen target and non target tissues (Sirigu et al, , 1982(Sirigu et al, , 1983(Sirigu et al, , 1991. The 3u-HSD only takes part in the activating mechanism in target organs, since it requires 5u-reduced steroids as optimal substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their principal cells share many morphological features with typical mucin secreting elements, except for some peculiar aspects of their secretory granules [15]. What we know about their secretion dates back to a few histochemical studies documenting the presence of acidic glycoproteins [16] bearing AB0 and Lewis oligosaccharides [17]. Demonstration of oxytocin reactivity suggests that urethral glands do not provide only mucus components.…”
mentioning
confidence: 99%